Water retention efficiency of green roof systems in "extensive" and "intensive" type covers - Rosatto, Héctor; Meyer , Maia; Laureda, Daniel; Cazorla, Laura; Barrera, Daniel; Gamboa, Paula; Villalba, Gustavo; Bargiela, Martha; Pruzzo, Laura; Rodríguez Plaza, Luis; Mazzeo, Nadia; Caso, César; et al. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Flash floods in urban areas caused by overload of drainage networks are a recurrent problem of raising importance. Greenroofs retain part of the stormwater, lowering surface flow and generating runoff hydrographs with lower and delayed peak flows. Therefore, this technology can contribute to mitigate the overload of drainage networks. The results of the study that was carried out in City of Buenos Aires along almost two years, showed that the retention capacity of the tested lots tasted varied, depending upon precipitation, coverage and depth of the substrate. With precipitation less than or equal to 20 mm, the retention fraction was high (73% to 100%), and when precipitation reached 35 to 40 mm, the maximum percentage of retention was around 60%. However, when the rainfall was approximately 100 mm, the retention fraction was reduced substantially, reaching values nearing 30%. The results of the test showed that green roofs system represent a good alternative in the integrated management of water runoff in urban watersheds.